Isolation and characterization of an R-prime plasmid from Rhizobium meliloti. - Kiss, G B (1980)
Using a simple enrichment procedure, we isolated an R-prime derivative of plasmid R68.45 carrying a 17.8-megadalton segment of the Rhizobium meliloti 41 chromosome. The chromosomal segment carried on this plasmid (pGY1) includes the markers cys-24+, cys-46+, and att16-3. Plasmid pGY1 mobilized the chromosome in a polarized way starting from the region of homology, but cannot promote chromosome transfer from other sites. The att16-3 site on pGY1 allowed the integration of phage 16-3 into pGY1, and a composite plasmid of 91.8 megadaltons was formed. This vector (pGY2) is suitable for the introduction of Rhizobium bacteriophage 16-3 into other gram-negative bacteria.